Some Operations on Mixed Monotone Operator in Banach Spaces (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
This paper discusses some operations on mixed monotone operator in Banach space, especially addition an multiplication operations. We will prove the sum and product of two mixed monotone operators. The proof using some relevant definitions. The result is the sum o of them is a mixed monotone operator and the product is  too if both  satisfy some conditions
Keywords: nondecreasing and nonincreasing; Mixed monotone operator; Banach space; partial ordering